Survival benefit from abemaciclib in non–small cell lung cancer by Kirsten rat sarcoma–mutation gene expression subtype: retrospective analysis from the JUNIPER Trial - Liu, Jiangang; Wang, Hong; Aggarwal, Amit; Ortiz-Ruiz, Maria Jesus; Zapatero-Solana, Elisabet; Lallena, Maria Jose; Peregrina, Sandra; del Hoyo, Gloria Martinez; Velasco, Susana; Ebert, Philip J.; Gong, Xueqian; Hossain, Anwar M.; et al. (Frontiers in Oncology, 2025)
PurposeJUNIPER, a randomized, phase III trial of patients with stage IV non–small cell lung cancer and a detectable Kristen rat sarcoma (KRAS) mutation in codons 12 or 13 whose condition progressed after platinum-based chemotherapy and up to 1 additional therapy (could include immune checkpoint inhibitors), reported prolonged progression-free survival (PFS) but not overall survival (OS) among patients who were receiving abemaciclib versus those who were receiving erlotinib. To establish whether certain patient subgroups received an OS benefit from the addition of abemaciclib to best supportive care, JUNIPER patients were retrospectively evaluated for KRAS co-mutation gene expression subtype, and abemaciclib efficacy was assessed for each patient subgroup.Materials and methodsOf the 453 patients enrolled in the JUNIPER trial, tumor specimens for biomarker analysis were available for 148 (abemaciclib arm, n=79; erlotinib arm, n=69). Samples were profiled for gene expression and classified into 3 previously identified expression subtypes (KL, KP, and K). Tumor response, OS, and PFS were assessed within each subtype.ResultsRetrospective analyses of expression subtypes revealed an OS advantage for patients with KL subtype tumors who were receiving abemaciclib versus those with the KL subtype who were receiving erlotinib (median, 13.05 vs 5.65 months; hazard ratio, 0.25; 95% confidence interval, 0.09–0.73; P=.011). KL and KP expression subtype groups derived a PFS benefit from abemaciclib versus erlotinib (KL median, 6.64 vs 2.1 months; hazard ratio, 0.12; 95% confidence interval, 0.03–0.41; P=.001, and KP median, 5.52 vs 2.24 months; hazard ratio, 0.44; 95% confidence interval, 0.23–0.84; P=.013). Patients with K subtype tumors received no OS or PFS benefit from abemaciclib treatment.ConclusionsPatients with KL expression subtype tumors may derive better OS and PFS from abemaciclib versus erlotinib in KRAS-mutated non–small cell lung cancer. These results should be further validated in an independent dataset.